2023
DOI: 10.1186/s40510-023-00485-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective contribution ratio of the molar during sequential distalization using clear aligners and micro-implant anchorage: a finite element study

Xulin Liu,
Junjie Wu,
Yuxun Cheng
et al.

Abstract: Introduction This study aims to investigate the biomechanical effects of anchorage reinforcement using clear aligners (CAs) with microimplants during molar distalization. And also explores potential clinical strategies for enhancing anchorage in the sequential distalization process. Methods Finite element models were established to simulate the CAs, microimplants, upper dentition, periodontal ligament (PDL), and alveolar bone. In group set I, the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Similarly, the reciprocal force acted on the central incisor passed occlusally to the center of resistance, resulting in labial tipping and intrusion of the central incisor. Previous biomechanical analysis and clinical research have con rmed the results of this study [11,13,34].…”
Section: Disscussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, the reciprocal force acted on the central incisor passed occlusally to the center of resistance, resulting in labial tipping and intrusion of the central incisor. Previous biomechanical analysis and clinical research have con rmed the results of this study [11,13,34].…”
Section: Disscussionsupporting
confidence: 79%
“…Moreover, since the Class II elastic traction was directly applied onto the canine, the canine exhibited more lingual tipping, distal tipping and extrusion in the button group. Other biomechanical studies had con rmed this result [13,37]. Thus, we suggest that Class II elastic traction is able to enhance molar distalization and to prevent anchorage loss (proclination) of the anterior teeth.…”
Section: Disscussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies have shown that when using clear aligners to distalize molars and intrude anterior teeth, sequential molar distalization ( Liu et al, 2023 ) and distributed anterior teeth intrusion ( Liu and Hu, 2018 ) are more sensible than overall movement. Therefore, different distributed movement patterns were designed in this study to investigate the influence of tooth movement patterns on expansion with clear aligners.…”
Section: Discussionmentioning
confidence: 99%